Strategi Guru Pendidikan Agama Islam dalam Menanamkan Nilai Toleransi di SDN 130 Batununggal Kota Bandung - Anisa Nur Shaleha; Fajar Muhammad Mugni; Rahmat Hidayat (Jurnal Dirosah Islamiyah, 2025)
This research is motivated by the need to instill an attitude of tolerance in schools because of the diversity in students. The purpose of this research is to understand in depth how strategies are used by Islamic Religious Education (PAI) teachers in instilling the values of tolerance in elementary school students. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through interviews, observations and documentation studies. The results of the study show that the strategies used by PAI teachers in instilling tolerance values include incorporating tolerance values into learning materials, applying active learning methods that are in accordance with students' lives, and accustoming students to be respectful of each other in daily activities. In addition, PAI teachers also involve parents in supporting the process of implementing the value of tolerance.